Efectividad en la reducción de carga bacteriana con láser diodo versus hipoclorito de sodio. revisión bibliográfica - Arboleda Segura, Anghel Enrique (2025)
Objective: To determine the effectiveness of reducing bacterial load in root canals using diode laser treatment versus a traditional sodium hypochlorite irrigation technique. Materials and methods: This literature review will employ a search of the EBSCO HOST and PUBMED databases for systematic reviews of the effectiveness of bacterial load reduction with diode laser versus sodium hypochlorite. Articles published in the last 10 years will be collected. A thorough and detailed search with all variant terms will be performed. Results: A total of 60 articles were collected, through the process of inclusion and exclusion of articles based on the PRISMA method which added 19 relevant articles to the research. Conclusion: In the present study it can be concluded that both the efficacy of NaOCL and the diode laser, depending on their wavelengths, improve the properties of the irrigation substances and at the same time allow correct treatment and total elimination of smear smear, with the result that both are suitable for disinfection treatment and are effective in eliminating microorganisms present in the root canals.